2005
DOI: 10.1016/j.jaci.2005.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Allergen exposure in infancy and the development of sensitization, wheeze, and asthma at 4 years

Abstract: Background: The relationship between mite and pet allergen exposure in infancy and the subsequent development of sensitization and asthma is complex. Objective: We prospectively investigated the effect of allergen exposure at 3 months of age on the development of sensitization, wheeze, and physician-diagnosed asthma in the first 4 years of life in a birth cohort of children with and without an atopic mother. Methods: Children participated in the Prevention and Incidence of Asthma and Mite Allergy study. Allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
3
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 29 publications
(56 reference statements)
8
100
3
5
Order By: Relevance
“…The German Multi-Center Allergy Study (1844,1845) and the Dutch PIAMA study (1846) reported a dose-response relationship between early cat exposure and sensitization in children. In another study, feather pillow use and the ownership of pets with fur did not increase the risk of developing allergic rhinitis (1847).…”
Section: Early Exposure Of Petsmentioning
confidence: 99%
“…The German Multi-Center Allergy Study (1844,1845) and the Dutch PIAMA study (1846) reported a dose-response relationship between early cat exposure and sensitization in children. In another study, feather pillow use and the ownership of pets with fur did not increase the risk of developing allergic rhinitis (1847).…”
Section: Early Exposure Of Petsmentioning
confidence: 99%
“…This has been suggested by the ''high-dose tolerance'' hypothesis put forward for exposure to the cat allergen [44]. Nevertheless, whether this hypothesis can be applied to other aeroallergens is not clear and still controversial [45].…”
Section: Biological Pollutantsmentioning
confidence: 99%
“…Na análise do contato dentro de casa com animais no presente, verificou que a exposição domiciliar atual a animais é um fator de risco significante para o desenvolvimento de asma ativa. Os animais domésticos são considerados fontes de alérgenos intradomiciliares, e a relação entre a exposição aos mesmos na infância e desenvolvimento de sensibilização e sintomas de asma ainda são complexas 42 . Fatores como época da chegada do animal no domicilio, idade da criança à exposição, número de animais, carga alergênica do ambiente e história familiar de atopia podem modular a expressão da sensibilização a esses alérgenos 43,44 .…”
Section: Discussionunclassified